DIDACTIC CONDITIONS OF APPLICATION OF INFORMATION TECHNOLOGIES IN THE PROCESS OF HIGHER EDUCATION STUDENTS - Poberezhna, N.O. (Pedagogy of Higher and Secondary Education, 2009)
In the article the methods and complex of didactic conditions of information technology appliance in the educational process of students in a higher educational establishment have been elaborated and represented.